Noninvasive detection of graft injury after heart transplant using donor‐derived cell‐free DNA: A prospective multicenter study. Issue 10 (8th April 2019) - Khush, Kiran K.; Patel, Jignesh; Pinney, Sean; Kao, Andrew; Alharethi, Rami; DePasquale, Eugene; Ewald, Gregory; Berman, Peter; Kanwar, Manreet; Hiller, David; Yee, James P.; Woodward, Robert N.; et al.
Abstract : Standardized donor‐derived cell‐free DNA (dd‐cfDNA) testing has been introduced into clinical use to monitor kidney transplant recipients for rejection. This report describes the performance of this dd‐cfDNA assay to detect allograft rejection in samples from heart transplant (HT) recipients undergoing surveillance monitoring across the United States. Venous blood was longitudinally sampled from 740 HT recipients from 26 centers and in a single‐center cohort of 33 patients at high risk for antibody‐mediated rejection (AMR). Plasma dd‐cfDNA was quantified by using targeted amplification and sequencing of a single nucleotide polymorphism panel. The dd‐cfDNA levels were correlated to paired events of biopsy‐based diagnosis of rejection. The median dd‐cfDNA was 0.07% in reference HT recipients (2164 samples) and 0.17% in samples classified as acute rejection (35 samples; P  = .005). At a 0.2% threshold, dd‐cfDNA had a 44% sensitivity to detect rejection and a 97% negative predictive value. In the cohort at risk for AMR (11 samples), dd‐cfDNA levels were elevated 3‐fold in AMR compared with patients without AMR (99 samples, P  = .004). The standardized dd‐cfDNA test identified acute rejection in samples from a broad population of HT recipients. The reported test performance characteristics will guide the next stage of clinical utility studies of the dd‐cfDNA assay. Abstract : A large multicenter study in a broad heart transplant surveillance population demonstrates the ability of standardized donor‐ derived cell‐free DNA testing to identify both T cell–mediated and antibody‐mediated acute rejection with a high negative predictive value.